Pengaruh Penggunaan Teknologi Mobile Apps Dalam Meningkatkan Partisipasi Dan Keterlibatan Orang Tua Dalam Pendidikan Anak - Baso Intang Sappaile; Azhariah Rachman; Yenik Pujowati; Andi Muh Akbar Saputra; Rahmah Fitria; Nining Andriani (Departement of Mathematics Education, 2023)
Children's education is a shared responsibility between schools and parents. However, parents often face obstacles in being actively involved in their children's education. This study aims to examine the effect of using mobile apps technology in improving parents' participation and involvement in their children's education. Using the literature research method, this article reviews various related studies that discuss the effects of using mobile apps technology on parents' participation and involvement in children's education.